Assessing the impact of marketing and advertising as strategic approaches to Eurocities development: an Iberian case study approach. (29th October 2022) - Castanho, Rui Alexandre; Vulevic, Ana; Gomez, José Manuel Naranjo; Cabezas, José; Fernández-Pozo, Luis; Loures, Luís; Lousada, Sérgio António Neves; Escórcio, Patrícia Carlota; Kurowska-Pysz, Joanna
European city systems belong to different sovereign territories. Apart from that, geographical location and cultural sharing may become drawbacks for cross-border cooperation (CBC) projects in Eurocities. In this regard, the marketing research is perceived as a recommendation and does not become the basis of territorial development strategies. However, marketing and advertising are critical factors that can influence the CBC success. Thus, the impact of cooperative marketing forms in the CBC societies was analysed in five Iberian Eurocities, considering not only a literature review, data evaluation and visits to the areas of study, but also the analysis of experts and perceptions of main actors related to the CBC process. This study allowed to assess and determine how factors of marketing and advertising influence the regional development. Regions with more territorial success were identified and the data obtained provided a sustainable basis on how to use marketing and advertising tools for the cross-border regions development.